Coastal‐trapped behavior of the diurnal internal tide at O'ahu, Hawai'i. Issue 5 (22nd May 2017) - Smith, Katharine A.; Merrifield, Mark A.; Carter, Glenn S.
Abstract: The influence of rotation on the structure and propagation of internal tides around O'ahu, Hawai'i is investigated using in situ observations and a tidally forced, primitive equation model with realistic bathymetry and stratification. Particular attention is given to the diurnal internal tide, which largely has been de‐emphasized in previous studies of the region because of the dominance of the semidiurnal internal tide but has been determined by recent studies to be a significant contributor to baroclinic variability. Though both diurnal and semidiurnal internal tides are generated primarily over Ka'ena Ridge to the northwest of the island, the diurnal internal tide propagates clockwise around the island as an imperfectly trapped wave, while the semidiurnal internal tide propagates away from the ridge, unaffected by rotation. The diurnal and semidiurnal internal tides fall into the superinertial frequency range; however, the diurnal frequency apparently is sufficiently close to inertial (∼ 1.4 f ) for rotation to affect internal tide propagation. The in situ observations support the model finding that diurnal trapping provides the primary source of baroclinic variability along the eastern coast of the island, a stretch of coastline otherwise sheltered from the internal tide energy generated over the Hawaiian Ridge. The findings in Hawai'i suggest that coastal trapping of superinertial internal tides may be a significant source of variability and mixing in other nearshore systems around the world. Key Points: Model and observations show the diurnal internal tide propagates clockwise around O'ahu as an imperfectly trapped wave This coastal trapping has consequences for the island's nearshore variability Imperfect trapping of superinertial internal tides may be an overlooked phenomenon at other locations worldwide